Pengaruh Suhu Pemadatan terhadap Stabilitas Marshall pada Aspal Hibrida Self-Healing Hidrofobik - Yosef Aryawanda; Ratnawulan, Ratnawulan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of compaction temperature on Marshall stability in hydrophobic self-healing hybrid asphalt using a quantitative laboratory experimental approach. The asphalt mixture was formulated with penetration grade 60/70 binder and standard aggregates, modified by nanosilica to enhance hydrophobic characteristics and Escherichia coli as a biological self-healing agent. Compaction temperatures of 180°C, 185°C, and 190°C were evaluated alongside a 150°C control sample without modification. The results indicate a non-linear relationship between temperature and mechanical performance, with stability increasing to an optimum condition at 185°C before declining at higher temperatures. This trend reflects improved densification and aggregate interlocking at moderate temperatures, while excessive heat reduces binder effectiveness due to softening. Volumetric parameters further demonstrate that optimal temperature conditions contribute to balanced void distribution and improved binder efficiency. Additionally, the hybrid system exhibits multi-scale interactions between nano-modification and microbial healing mechanisms, enhancing durability and resistance to environmental factors. These findings emphasize the importance of precise thermal control in optimizing both structural integrity and functional performance of advanced asphalt materials.